FROM TRAUMATIC TO NARRATIVE MEMORIES:: THE RHETORICAL FUNCTION OF BIRTH METAPHORS IN MICAH 4-5 - Claassens, L J (Acta Theologica, 2018)
This article proposes that trauma hermeneutics and, in particular, greater theoretical reflection on the relationship between trauma and metaphor may help explain the birth metaphors in Micah 4:9-5:3, where the woman-in-labour metaphor has been transformed quite dramatically. In the context of Micah, which I propose could also be characterized as trauma literature, there is evidence of a movement from potentially debilitating traumatic memories, associated with the woman-in-labour metaphor, to memories that have been integrated into some kind of narrative framework and that may potentially be considered to be a sign of healing and recovery.